MiR-146b overexpression promotes bladder cancer cell growth via the SMAD4/C-MYC/Cyclin D1 axis - Zhu, Junlan; Zheng, Zhijian; Yin, Zhangya; Ding, Linchao; Li, Congya; Wang, Xuyao; Shu, Peng; Zhou, Jun; Liu, Weihua; Liu, Jian (Frontiers in Oncology, 2025)
MiR-146b has been identified as being overexpressed in human bladder cancer (BCa) and implicated in promoting cancer cell invasion. However, its specific involvement in BCa cell growth remains unclear. In this study, we demonstrate that the downregulation of miR-146b significantly suppresses tumorigenic growth of human BCa cells both in vitro and in vivo by inducing G0/G1 cell cycle arrest. Specifically, miR-146b inhibition resulted in a significant reduction in colony formation (p < 0.05) and anchorage-independent growth in both UMUC3 and T24T cells, as measured by soft agar assays, with three independent replicates for each experiment. Notably, Cyclin D1 protein plays a crucial role in miR-146b-induced BCa cell proliferation, as confirmed by Western blotting (p < 0.05), with each experiment performed in triplicate. Mechanistic investigations reveal that miR-146b reduces mothers against decapentaplegic homolog 4 (SMAD4) mRNA stability by directly binding to its 3′ untranslated region (3′-UTR), leading to decreased SMAD4 expression. This reduction in SMAD4 levels promotes cellular myelocytomatosis (C-MYC) transcription, which in turn enhances Cyclin D1 transcription, ultimately facilitating BCa cell proliferation. The findings unveil a novel regulatory axis involving SMAD4/C-MYC/Cyclin D1 in mediating the oncogenic role of miR-146b in BCa cells. Statistical significance was determined using Student’s t-test, with p-values <0.05 considered significant. Together with its previously established function in BCa invasion, the results highlight the potential for developing miR-146b-based therapeutic strategies for treating human BCa patients.